2020
DOI: 10.1161/hypertensionaha.120.15236
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Isolevuglandins Contribute to Vascular Oxidative Stress and Mitochondria-Targeted Scavenger of Isolevuglandins Reduces Mitochondrial Dysfunction and Hypertension

Abstract: Hypertension remains a major health problem in Western Societies, and blood pressure is poorly controlled in a third of patients despite use of multiple drugs. Mitochondrial dysfunction contributes to hypertension, and mitochondria-targeted agents can potentially improve treatment of hypertension. We have proposed that mitochondrial oxidative stress produces reactive dicarbonyl lipid peroxidation products, isolevuglandins, and that scavenging of mitochondrial isolevuglandins improves vascular function and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 74 publications
2
18
0
Order By: Relevance
“…This is notable, as urinary F2-isoprostane is reduced by treatment with the non-specific antioxidant alpha tocopherol (39,40). These data support the idea that the beneficial effects of PPM are not due to general inhibition of lipid peroxidation or metal ion chelation but to reactive lipid (11,31,38,41,42).…”
Section: Results In Tecs and Lecs Indicate That The Highly Reactive L...supporting
confidence: 62%
“…This is notable, as urinary F2-isoprostane is reduced by treatment with the non-specific antioxidant alpha tocopherol (39,40). These data support the idea that the beneficial effects of PPM are not due to general inhibition of lipid peroxidation or metal ion chelation but to reactive lipid (11,31,38,41,42).…”
Section: Results In Tecs and Lecs Indicate That The Highly Reactive L...supporting
confidence: 62%
“…In RVLM, transcriptional upregulation of sod2 protects against mitochondrial oxidative stress and hypertension in Ang II treatment in normotensive rats [ 61 ]. SOD2 also participates in the protection again hypertension and cardiovascular complications conferred by the mitochondria-target antioxidants [ 62 ]. Nrf2 is the master regulator of antioxidant genes and, hence, of antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…To test the pathological role of mitochondrial isolevuglandins we developed mitochondria-targeted scavenger of isoLGs, mito2HOBA. It was found that mito2HOBA reduces protein-isolevuglandins adducts, improves deacetylation of mitochondrial proteins, improves mitochondrial and endothelial functions, and reduces hypertension [ 23 ▪▪ ]. We propose that metabolic conditions downregulate Sirt3 activity due to decrease in NAD+ and increase in Acetyl-CoA while oxidative stress causes redox inactivation of Sirt3.…”
Section: Impairment Of Sirt3 In Pathological Conditionsmentioning
confidence: 99%
“…In recent studies, we proposed that oxidative stress can directly contribute to Sirt3 inactivation due to formation of harmful lipid peroxidation products, isolevuglandins, in mitochondria. We discovered 250% increase in mitochondrial isolevuglandins in arterioles isolated from patients with essential hypertension [ 23 ▪▪ ]. Interestingly, scavenger of mitochondrial isolevuglandins, mito2HOBA, protects Sirt3 activity, improves SOD2 deacetylation and inhibits endothelial oxidative stress.…”
Section: Impairment Of Sirt3 In Pathological Conditionsmentioning
confidence: 99%